Manajemen Komunitas Pemberdayaan Perempuan Nurul Huda Dalam Meningkatkan Ketahanan Pangan Di Desa Martebing Serdang Bedagai - Syauqi Az Zahra; Erwan Efendi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Family food security is a strategic issue closely related to the welfare of rural communities and the role of women in managing local food sources. This study aims to analyze how the management of the Nurul Huda women's empowerment community plays a role in improving family food security in Martebing Village through a da'wah management approach. This study used a qualitative method with a descriptive approach, through field observations, in-depth interviews with community administrators and members, and activity documentation. The results show that the Nurul Huda community carries out functional management functions, including activity planning, role organization, program implementation, and collective evaluation integrated with da'wah values. These functions are directly implemented in women's empowerment practices through family food security management, such as urban farming and yard utilization. Women play an active role in the entire process, thus encouraging independence and sustainability of family food security. This study concludes that the integration of da'wah management and women's empowerment in the Nurul Huda community contributes significantly to strengthening family food security and has the potential to become a model for community-based empowerment in rural areas.